2008
DOI: 10.1152/ajpheart.00193.2008
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of blood borne microparticles as markers of premature coronary calcification in newly menopausal women

Abstract: While the risk for symptomatic atherosclerotic disease increases after menopause, currently recognized risk factors do not identify ongoing disease processes in low-risk women. This study tested the hypothesis that circulating cell-derived microparticles may reflect disease processes in women defined as low risk by the Framingham risk score. The concentration and phenotype of circulating microparticles were evaluated in a cross-sectional study of apparently healthy menopausal women, screened for enrollment int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
116
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(123 citation statements)
references
References 44 publications
4
116
0
3
Order By: Relevance
“…Flow cytometric analyses demonstrated that the majority of MVs isolated from CLL plasma were positive for annexin V binding (typically, Ͼ90%; Figure 1A), and sizes were within 1.0 m, typical characteristics of MVs, 2 on the basis of forward/side scatter with the use of 1.0-m standard beads. 13 These were heterogeneous, membrane-encapsulated small vesicles ranging in size from 0.1 to 1.0 m as revealed under electron microscopy ( Figure 1B), also typical features of MV. Although significantly greater levels (P Ͻ .006) of MVs were demonstrable in the majority of CLL plasma ( Figure 1C), we could not find a significant association of MV levels with disease stage or other prognostic factors (data not shown).…”
mentioning
confidence: 83%
“…Flow cytometric analyses demonstrated that the majority of MVs isolated from CLL plasma were positive for annexin V binding (typically, Ͼ90%; Figure 1A), and sizes were within 1.0 m, typical characteristics of MVs, 2 on the basis of forward/side scatter with the use of 1.0-m standard beads. 13 These were heterogeneous, membrane-encapsulated small vesicles ranging in size from 0.1 to 1.0 m as revealed under electron microscopy ( Figure 1B), also typical features of MV. Although significantly greater levels (P Ͻ .006) of MVs were demonstrable in the majority of CLL plasma ( Figure 1C), we could not find a significant association of MV levels with disease stage or other prognostic factors (data not shown).…”
mentioning
confidence: 83%
“…Several lines of evidence suggest that PMPs contribute to the pathogenesis of atherothrombosis. Indeed, plasma PMPs are elevated in patients with established cardiovascular disease compared with healthy controls (18,19) and are positively correlated with the atherosclerotic burden (20). More importantly, preliminary results suggest that higher PMPs are associated with higher risk for cardiovascular events (18).…”
Section: Introductionmentioning
confidence: 94%
“…Each KEEPS participant underwent a medical examination, including body morphometrics (BMI, waist/hip ratio measurements), an MRI scan, standard blood chemistries, highresolution B-mode ultrasound for the assessment of CIMT and CT for the assessment of CAC. 21,22 All CAC and CIMT results were read centrally by individuals blinded to participant demographics. 22 None of the women in the Mayo Clinic KEEPS-MRI study developed a neurologic or psychiatric disorder such as stroke or depression throughout the duration of the study.…”
mentioning
confidence: 99%
“…24 Expression of activated platelet membrane glycoprotein IIb/IIIa complex binding to PAC-1 antibody (an indirect measure of the fibrinogen receptor complex) was measured by flow cytometry. 17,21,24 Blood-borne microvesicles. Numbers of activated plateletderived microvesicles and total numbers of thrombogenic (phosphatidylserine-positive defined by annexin V binding) microvesicles were obtained at baseline using binding of fluorophoreconjugated, platelet-specific CD42a antibody and recombinant annexin V, respectively, by flow cytometry.…”
mentioning
confidence: 99%